Avaliação do geomorfossítio da caverna Serra das Andorinhas – municipio de São Geraldo do Araguaia/PA - Alencar, Diêmison Ladislau (2021)
The Serra das Andorinhas Cave is located at coordinates 6°5'25” to the South and 48°30'37” to the West, in the SW sector of the PESAM, an area where extensive steep reliefs are concentrated, appearing in abrupt sectors characterized by escapes in geoforms in the plateau. The importance of the research is justified by the need to carry out an integrated analysis of the landscape that comprises the Serra das Andorinhas Cave as a geomorphosity, highlighting its values, the environmental conditions and aspects that may justify the need to protect the area. The general objective of the research was to carry out an evaluation of the geomorphosity of the Serra das Andorinhas cave, in order to measure the real values as an area of geomorphological interest. The main theories that guide the concept of Geodiversity, Geoconservation and its relationship with the Geomorphological Heritage were approached from a geographic-geomorphological perspective focused on the Brazilian karst reliefs. The conceptualization of karst reliefs, their distribution in the territory, as well as their lithologies were also discussed. In sequence, the processes and formations of the karst landscapes were approached, emphasizing the internal and external vision and their joint and isolated processes. With regard to the methodological procedures, an inventory of an evaluation form of geomorphological interest was prepared in the Serra das Andorinhas cave, in which the qualitative value of all existing values in the area was recorded. In sequence, a general characterization of the Municipality of São Geraldo do Araguaia was presented, highlighting its physical and social attributes, where, then, the Serra dos Martírios/Andorinhas and the APA Araguaia were characterized. The results obtained high values of geomorphological relevance, having large assigned values that are justified in the text. The inventory methodology proposed by Pereira (2006) was successfully applied after carrying out adaptations (such as removing the numerical form of quantitative evaluation) aimed at the reality of the studied area, always believing that the methodologies followed by referring authors must be adapted according to the development of scientific works. The elaboration of this dissertation is an initial work on the evaluation of the geomorphosites of the Serra dos Martírios/Andorinhas State Park and Araguaia Environmental Protection Area. Despite all the adversities and setbacks that occurred throughout this research, the work managed to achieve the proposed objectives.